The Impact of Coretax Implementation on Reporting of Annual Tax Returns for Corporate Taxpayers in Riau Province: PENGARUH IMPLEMENTASI CORETAX TERHADAP PELAPORAN SPT TAHUNAN WAJIB PAJAK BADAN DI PROVINSI RIAU - Arifqi, Fikri (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Abstract. This study aims to examine the impact of Coretax implementation on the filing of Annual Tax Report (SPT) by Corporate Taxpayers in Riau Province. Coretax is a digital technology innovation developed by the Directorate General of Taxes as an effort to modernize the previously used tax administration system. This system integrates all key tax administration processes including taxpayer registration, annual return filing, tax payment, as well as audit and collection into a unified platform. However, upon its launch in early January 2025, numerous reports highlighted technical and operational challenges in using Coretax. Common issues included system disruptions, data inconsistencies, and insufficient outreach and training for taxpayers. These obstacles have sparked skepticism among the public regarding Indonesia’s tax system transformation, which was expected to become more transparent, accurate, and efficient. Although the filing of Annual Tax Report through Coretax is only set to begin for the 2025 tax year, several services such as taxpayer registration, tax invoice issuance, monthly report filing (SPT Masa), and tax payments have already been integrated into the Coretax. Abstrak. Penelitian ini bertujuan untuk mengkaji dampak penerapan Coretax terhadap pelaporan Surat Pemberitahuan (SPT) Tahunan oleh Wajib Pajak Badan di Provinsi Riau. Coretax merupakan inovasi teknologi digital yang dikembangkan oleh Direktorat Jenderal Pajak sebagai upaya pembaruan sistem administrasi perpajakan yang sebelumnya digunakan. Sistem ini mengintegrasikan seluruh proses utama administrasi perpajakan, mulai dari pendaftaran Wajib Pajak, pelaporan SPT, pembayaran pajak, hingga pemeriksaan dan penagihan pajak dalam satu platform terpadu. Akan tetapi pada saat peluncuran Coretax di awal bulan Januari tahun 2025, banyak laporan yang mengungkap kendala teknis dan operasional dalam penggunaan Coretax. Beberapa masalah yang sering muncul antara lain gangguan sistem, ketidaksesuaian data, dan sosialisasi serta pelatihan kepada Wajib Pajak yang dirasa kurang. Hal ini menimbulkan skeptisme ditengah masyarakat terhadap transformasi sistem perpajakan Indonesia uang diharapkan lebih transparan, akurat, dan efisien. Walapun pelaporan SPT Tahunan pada Coretax baru diimplementasikan untuk pelaporan tahun pajak 2025, namun beberapa layanan seperti pendaftaran wajib pajak, penerbitan faktur pajak, pelaporan SPT Masa, dan pembayaran pajak telah menggunakan Coretax. .